Subtle features of delamination in cross-ply laminates due to low speed impact - Sitnikova, Elena; Li, Shuguang; Li, Dafei; Yi, Xiaosu (Elsevier, 2017)
In cross-ply laminates, the shape of delamination areas, which form due to low velocity impact, have two subtle features, which have been observed consistently in numerous experiments. Those are the pointed delamination tips and the intact zone between the lobes of delamination. However, there have not been any account available in the literature how they can be consistently captured through numerical modelling, and hence these features in published modelling results were often absent. It is the objective of this paper to identify the underlying modelling considerations so that these features can be captured with confidence. A key and unique reason has been identified in each case. Namely, inclusion of intra-laminar damage allows to reproduce the pointed delamination tips, while the gap between the lobes of delamination can be captured by models with sufficiently refined mesh, where friction between the laminas is taken into account. The capability of capturing these subtle features helps to raise the level of fidelity on the simulation of delamination due to impact.